Soil Properties Influence Vertical Distribution of Boron Fractions in Lateritic Soil - Sahu, Mamta; Kundu, Manik Chandra; C. P. , Mohammed Nisab (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted at Palli Siksha Bhavana (Institute of Agriculture), Visva-Bharati, West Bengal, India, during 2019-20 to evaluate the different fractions of boron (B) along depth and their relationship to some soil properties in lateritic soils of West Bengal, India. The sequential B fractionation scheme was followed to estimate B fractions in the studied soils. It was found that most of the soils fall under the sandy clay loam and clay loam soil textural categories. The soil pH was either categorized as extremely acidic or slightly acidic in nature and the range of low to medium organic carbon content was present. The studied soils’ CEC varied between 5.90 to 26.64 [C mol (P+) kg-1]. In the B fractionation study, it was revealed that, for uptake of plants, the readily soluble boron (Rs-B) is the most easily accessible fraction among all other fractions, and the residual boron (Res-B) fraction accounts for the major portion of total soil boron (Tot-B). Different soil properties of the study area greatly influenced the B fractions along soil depths. The contribution of different B fractions towards total soil B (Tot-B) B followed the order: residual boron (Res-B) >> oxide-bound boron (Oxd-B) > organically bound boron (Org-B) > specifically adsorbed boron (Sad-B) > readily soluble boron (Rs-B). The current study will be helpful for adopting the fertilizer management practices of boron-deficient lateritic soils (Alfisols).